2004
DOI: 10.1093/aje/kwh055
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated Health among Young People with Type 1 Diabetes in Relation to Risk Factors in a Longitudinal Study

Abstract: Care for type 1 diabetes mellitus should both alleviate the physical complications of the disease and improve overall quality of life. The Wisconsin Diabetes Registry, comprising a population-based cohort that is followed longitudinally from diagnosis of type 1 diabetes, provided the authors with a unique opportunity to examine quality of life in children, adolescents, and young adults with type 1 diabetes and its relation to both sociodemographic and clinical risk factors. The authors analyzed data from 1987-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
51
2
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 29 publications
9
51
2
10
Order By: Relevance
“…The worst assessment of QoL among older adolescents was demonstrated in the largest study (12)(13)18,20) . Nevertheless, opposite results have also been found in literature (9,21) .…”
Section: Qol and Socio-demographic Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…The worst assessment of QoL among older adolescents was demonstrated in the largest study (12)(13)18,20) . Nevertheless, opposite results have also been found in literature (9,21) .…”
Section: Qol and Socio-demographic Factorsmentioning
confidence: 94%
“…A study has demonstrated that self-assessed health was better among white adolescents (p<0.012) (18) . Caucasian youths obtained better scores in the Impact and Worries domains (p< 0.05) (19) .…”
Section: Qol and Socio-demographic Factorsmentioning
confidence: 99%
“…One potential explanation for this finding is the relatively high scores of these HRQOL parameters at baseline compared with patients on CSII. Although speculative, this observation can be attributed to a relative short diabetes duration [7] . In a recent Cochrane review, CSII was preferred over MDI with respect to HRQOL [11] .…”
mentioning
confidence: 94%
“…Previous studies have underlined the importance of this association by revealing a negative association between HRQOL and diabetes prognosis [3][4][5] . In T1DM, a relevant deterioration of HRQOL and glycaemic control during the disease course has been reported [6,7] . In contrast, reports have also found no association between duration of diabetes and scores on quality of life scales [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence in teenagers has been increasing during the last decade [5]. Based on estimations, there is one diabetic case per 400 to 500 teenagers in the world [6]. Type1 diabetes is considered a chronic and difficult disease for teenagers and their families.…”
Section: Introductionmentioning
confidence: 99%